Association between HbA1c levels with severity of coronary artery disease and short-term outcomes of acute ST-elevation myocardial infarction in nondiabetic patients. (October 2015) - Ghaffari, Samad; Niafar, Farhad; Separham, Ahmad; Niafar, Mitra; Pourafkari, Leili; Nader, Nader D.
Background: The severity of coronary artery disease (CAD) is directly related to the quality of glucose control in diabetic patients. Additionally, mortality after an acute coronary syndrome is higher in patients with diabetes and it correlates to the level of glucose control. However, the role of higher gluconated hemoglobin in the process of coronary atherosclerosis and clinical outcome of acute myocardial infarction is unknown. Objectives: To evaluate the association of HbA1c level and severity of CAD and short-term outcomes of acute ST-elevation myocardial infarction (STEMI) in nondiabetics. Methods: A total of 290 nondiabetic patients with STEMI were prospectively enrolled following their admission. Patients were stratified into 2 groups based on the median percent of HbA1c (⩽5.8% 'Low' and >5.8% 'High'). The severity of CAD based on the Califf scoring system, in-hospital mortality and morbidities of STEMI were compared between groups. Patients were followed for 1 year after discharge to assess readmission and mortality rate. Results: The severity score for CAD was significantly higher in the 'High' versus 'Low' HbA1c group (7.7 ± 2.7 and 5.5 ± 2.6, p = 0.001). A total of 15 patients died in both groups during the follow-up period. While in-hospital mortality was similar between the two groups, 12-month mortality was significantly higher in the 'High' group (7.7% versus 2.7%, p = 0.043). In addition, the rehospitalization rate within 1 year was 8.8% in the 'Low' group, which was significantly lower than 19.0% in the 'High' group ( p = 0.016). Conclusion: Among nondiabetic patients presenting with STEMI, the severity of CAD was higher in those with HbA1c level >5.8%; 1-year mortality and hospital readmission rates were also higher in this group of patients.